Knowledge, attitude and practices regarding digital well-being features and their association with screen time and addiction in Maharashtra, India - Ambike, Amey; Rao, Shirish; Paranjape, Raghav; Adarkar, Shilpa (International Journal of Research in Medical Sciences, 2023)
Background: Digital service providers have come up with certain ‘digital well-being features’ as a step towards tackling harmful effects of screen overuse on physical and mental health. However, the awareness and use of the same remains scant. Our objective was to assess the knowledge, attitudes and practices regarding digital well-being features in the adult population of Maharashtra, India and the associations and correlations of the practice of using these features with screen time and degree of screen addiction. Methods: A cross-sectional online questionnaire-based study was conducted among 335 participants who were selected using quota sampling and were administered a smartphone addiction scale and a self-designed questionnaire at KEM Hospital, Mumbai. Results: More than 60% participants were aware about digital well-being features and had positive attitudes towards them. Total of 65.4% participants were digital wellbeing feature users. Correlation of digital hygiene score and digital wellbeing score was found neither with addiction nor with the average screen time. Conclusions: Knowledge, attitude and practices regarding digital well-being features were adequate among the urban population of Maharashtra. However, their use was not found to be associated with reduced screen time or a low screen addiction score. With further development and standardization, these features can be a useful tool for prevention of screen overuse and addiction.